Poorly Differentiated Sertoli-Leydig Cell Tumour of Ovary with Heterologous Elements - Sahoo, Tapan Kumar (J Clin Diagn Res, 2017)
Sertoli-Leydig Cell Tumour (SLCT) is included under sex-cord stromal tumour of testis or ovary. Ovarian pathology is an extremely rare entity constituting less than 0.5% of all ovarian neoplasms. Majority of the cases present at younger age group, i.e., 2(nd) and 3(rd) decade of life. The clinical presentation depends on either mass effect or excess hormone production. Virillization symptoms are the most common presentation and depend upon the quantity of androgen production. Most of the patients have a unilateral mass without extraovarian spread and present at stage-I. Treatment and prognosis depends on the degree of the differentiation and the stage of the disease. Here, we report a case of SLCT of the ovary in a young female. The patient initially presented with pain abdomen due to mass effect and was treated with conservative surgery followed by adjuvant chemotherapy due to the presence of poorly differentiated pathology with heterologous elements.